An Electrochemical Sensor Fabricated by Sonochemical Approach for Determination of the Antipsychotic Drug Haloperidol. Issue 3 (24th August 2022) - Incebay, Hilal; Ucar, Ayse
Abstract: A nanocomposite (Ho2 O3 NPs/BNT) was synthesized by decorating holmium(III)oxide nanoparticles (H2 O3 NPs) on bentonite (BNT) through a realizable sonochemical approach for the electrochemical detection of haloperidol (Hlp). A glassy carbon electrode was modified with this nanocomposite. The Ho2 O3 NPs/BNT modified electrode outperformed bare and other modified electrodes in terms of electrochemical performance for Hlp detection in a pH 8.0 phosphate buffer. The proposed electrochemical platform showed a wide linear range (0.01 μM–24 μM), low detection limit (2.4 nM), and high sensitivity by square wave voltammetry. In addition, the proposed electrochemical sensor met the clinical criteria in terms of stability, selectivity, and repeatability. Abstract :